2020
DOI: 10.1002/smll.202002517
|View full text |Cite
|
Sign up to set email alerts
|

An Electrodeposited MXene‐Ti3C2Tx Nanosheets Functionalized by Task‐Specific Ionic Liquid for Simultaneous and Multiplexed Detection of Bladder Cancer Biomarkers

Abstract: MXenes (with chemical formula M n+1 X n T x , where M = transition metals such as Ti, Sc, V, Nb, Mo, and Cr; X = C and/or N; T x = surface functional groups, such as OH, O, and minor F; n = 1, 2, or 3) are synthesized by selectively etching Agroup sp elements (typically group III A or IV A such as Al or Ga) from layered parent ternary MAX phases (with chemical formula Mn + 1AXn, where, A = elements from groups 13 and 14, such as Al, Ga, C, and Si). [3] To date, families of MXenes comprising more than 30 mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…In the fabrication of various electrochemical sensing devices, arranging nanomaterials into a particular position on a patterned electrode with controlled architecture, morphology, and thickness is a most challenging issue [97]. For obtaining large-scale and high-quality MXene nanosheets thin films, Sharifuzzaman, M. et al [97] reported a green, facile, and cost-effective one-pot deposition mechanism of Ti 3 C 2 nanosheets (Figure 20). They demonstrated that Ti 3 C 2 nanosheets can be precisely and uniformly deposited on different sensing electrodes at room temperature within a few minutes via electroplating technique using a DMSO suspension with colloidal Ti 3 C 2 nanosheets as an electrolyte.…”
Section: Flexible Electrochemical Sensors and Othersmentioning
confidence: 99%
See 2 more Smart Citations
“…In the fabrication of various electrochemical sensing devices, arranging nanomaterials into a particular position on a patterned electrode with controlled architecture, morphology, and thickness is a most challenging issue [97]. For obtaining large-scale and high-quality MXene nanosheets thin films, Sharifuzzaman, M. et al [97] reported a green, facile, and cost-effective one-pot deposition mechanism of Ti 3 C 2 nanosheets (Figure 20). They demonstrated that Ti 3 C 2 nanosheets can be precisely and uniformly deposited on different sensing electrodes at room temperature within a few minutes via electroplating technique using a DMSO suspension with colloidal Ti 3 C 2 nanosheets as an electrolyte.…”
Section: Flexible Electrochemical Sensors and Othersmentioning
confidence: 99%
“…In the fabrication of various electrochemical sensing devices, arranging nanomaterials into a particular position on a patterned electrode with controlled architecture, morphology, and thickness is a most challenging issue [97]. For obtaining large-scale and high-quality MXene nanosheets thin films, Sharifuzzaman, M. et al [97] reported a green, facile, and cost-effective one-pot deposition mechanism of Ti 3 C 2 nanosheets (Figure 20).…”
Section: Flexible Electrochemical Sensors and Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…20 To obtain better quality monolayer MXene, many new improvements have been proposed. N,N-Dimethylformamide (DMF), 21,22 N-methyl-2pyrrolidone (NMP), 23 and DMSO [24][25][26] are proved to be "good solvents" for Ti 3 C 2 T x akes by Gogotsi et al 27 Zhang et al successfully developed a tuned microenvironment method (TMM) for the preparation of highly concentrated MXene organic solvents to obtain a large delaminated product yield, which can easily achieve a yield of 63.9% for a single layer of MXene and close to 100% if the material is continuously collected. 21 Better solubility and single-layer MXene production will signicantly increase productivity and reduce costs, laying a good foundation for large-scale hardware fabrication.…”
Section: The Preparation Of Mxenementioning
confidence: 99%
“…Among them, 2D Ti 3 C 2 T x MXene nanosheets-based silk textiles, fabrics, and nanofibers have attracted much attention owing to their exciting combination of electrical, electrochemical (abundant surface functional groups), and mechanical properties. [22][23][24][25] The uniaxial elongation of the PNFs during the electrospinning process and enriched hydrogen (H) bond between PDFE and nanofillers reinforce the polar crystalline β-phase. [26] With the impregnation of MXene into PDFE electrospinning solution, the H bonds form between the electronegative surface terminations (OH, O, and F) of MXene with the positive H and F atoms in PDFE due to the strong electrostatic attraction.…”
Section: Introductionmentioning
confidence: 99%